DINAMIKA ISLAM POLITIK DAN ISLAM KULTURAL DI INDONESIA - LL Saefudin Zuhri (JURNAL INDO-ISLAMIKA, 2018)
This article discusses how the history of politics in Indonesia. The Islamic movement in Indonesia is so dynamic. This dynamic can be seen from the emerging Islamic movements, which can be grouped into two, namely the political Islam movement and cultural Islam. One of the dynamics that is still strongly discussed today is related to state ideology. Political Islam considers it necessary, while cultural Islam considers it unnecessary. Islam is most importantly embodied in the culture of society, not formalist. In conclusion, Islam does need to be embodied in cultural and political ways, but it does not need to be formalist. The two of them must complement each other. And The bigger the Islamic political movement at the ideological level causes the power of Muslims to weaken and experience stagnation. Therefore, in the Muslim struggle movement, another concept that moves culturally as an alternative is presented so that Muslims no longer experience delays in development.